EFFECTIVE WAYS TO DEVELOP LISTENING SKILLS IN ENGLISH (Modern education and development, 2025)
Listening is considered as one of the most important criteria during signifying candidates’ level of language proficiency. Not only in academic exams, but also in real life conversations, listening plays a crucial role in understanding speakers. This article suggests several approaches to help candidates improve their listening skills in their second language.